Durch Eye Tracking Einblicke ins wissenschaftliche Lesen gewinnen? : Eine Diskussion auf Grundlage bestehender Forschung - Introna, Silvia (Linguistik Online, 2025)
This paper discusses the potential for employing eye-tracking technology in the investigation of academic reading in higher education. The necessity to examine academic reading within this specific context has become evident due to its pivotal role in academic pursuits and the significant research gaps that persist in this field. For instance, while practitioners in higher education are well aware of the comprehension difficulties students face when reading academic texts, these challenges are rarely investigated empirically. In recent years, eye-tracking has become a well-established method in the field of reading research, as it enables the real-time measurement of readers’ eye movements while processing linguistic stimuli. Such measurements have the capacity to reveal patterns that may be indicative of comprehension difficulties. Beyond its application in L1 reading research, eye-tracking has also gained prominence in the fields of second language acquisition and multilingualism, offering valuable insights into natural reading processes in both L1 and L2 contexts. It is evident that using eye-tracking technology within the context of academic reading holds considerable potential for revealing specific challenges that both domestic and international students face when processing academic German texts.